Experience with Treatment of Retroperitoneal Fibrosis: Collaboration of Urology and Nephrology Departments for 26 years in Marmara University - ŞEKERCİ, ÇAĞRI AKIN; ŞİMŞEK, FERRUH; KOÇ, MEHMET; TANIDIR, YILÖREN (TURK NEFROLOJI DIYALIZ TRANSPLANTASYON DERGISI, 2017)
OBJECTIVE: Retroperitoneal fibrosis (RPF) is a rare condition characterized by the presence of inflammation and fibrosis in the retroperitoneum. This study describes our multidisciplinary approach and our results. MATERIAL and METHODS: Patients diagnosed with RPF at Marmara University between January 1990 and May 2007 were evaluated. Etiologies, demographic characteristics, renal functions, treatments and prognoses of each patient were recorded and data were analyzed. RESULTS: Of all patients, five were female, 15 were male and the mean follow-up was 11.3 years (1-18 years). Six patients were operated unilaterally and five were operated bilaterally with ureterolysis. Median creatinine values at diagnosis were 2.75 mg/dl (0.7-6.9 mg/dl) in females, 3.2 mg/dl (0.84-7.2 mg/dl) in males and 3.11 mg/dl (0.7-7.2 mg/dl) in the whole group. Median baseline creatinine level after surgery (n=11) was found to decrease from 3.63 mg/dl (1.4-7.2 mg/dl to 1.46 mg/dl (0.8-2.6 mg/dl). Baseline and drop in creatinine were compared among patients treated with either surgical or pharmacological methods, and no statistical significance was found. CONCLUSION: Retroperitoneal fibrosis can be treated surgically and pharmacologically. Our study has shown similar success for both methods. Treatment should be specific for each patient in a multidisciplinary fashion.
Keywords: Retroperitoneal fibrosis; Creatinine; Ureterolysis; Tamoxifen; PREDNISONE; TAMOXIFEN; DIAGNOSIS